"Making Socialists": Bill Pritchard, the Socialist Party of Canada, and the Third International - Campbell, J. Peter (Labour / Le Travail, 1992)
The legacy of the Socialist Party of Canada has come down to us in phrases such as economic determinism, mechanistic materialism, impossiblism, and sectarianism. The life of Bill Pritchard reveals the humanist roots of the SPC and what the party's leading thinkers owed to William Morris and the British ethical socialist tradition. That tradition was about `making socialists' who were educated, organized, and prepared to implement fully a socialist society. Bill Pritchard and other Marxian socialists, as much as they supported the Russian Revolution, were unwilling to submerge that goal in the program of the Third International. Their humanism, as much as their determinism, explains the choices they made and the legacy they left.
Keywords: ABSTRACTS; HUMANISM; LABOUR/LE Travail (Book); MORRIS; William; 1834-1896; PRITCHARD; Bill; REVOLUTIONARY literature; Russian; Socialism; Socialist Party of Canada